Law Enforcement and Justice Based on Local Wisdom in Protecting the Intellectual Property Rights of Batak Toba Ulos Weaving Fabric - Meli Gultom (Golden Ratio of Law and Social Policy Review, 2026)
Law enforcement aims to realize justice within society. However in practice, the rigid and formalistic application of positive law often fails to reflect the sense of justice living within the community Indonesia, as apluralistic state possesses rich cultural values and tradition known as local wisdom, which play a strategic role in achieving substansive justice. Local wisdom embodies noble values such as deliberation, balance, harmony and restoration of social relations, which align with the principles of restorative justice. Indonesia is a country that consists of various tribes and cultures so that it has priceless Traditional Cultural Expressions and really needs to be protected. One form of traditional cultural expression in Indonesia is ulos cloth, which is a fabric product that is known internationally. This study aims to analyze the concept of law enforcement and justice based on lacal wisdom and its relevance within the Indonesia legal system. The research employs a normative juridicial mthod using statutory, conceptual and sociological approaches. The finding indicate that integrating local wisdom into law enforcement strengthens legal legitimacy, enhances public trust in law enforcement institusions, and promotes a more humane, contextual, and socially responsive form of justice. Therefore law enforcement based on local wisdom is essential in creating a legal system that not only ensures legal certainty but also embodies the values of rooted in society. Ulos cloth is a traditional woven cloth typical of North Sumatra which is currently widely used by fashion designers as part of their creations. Ulos cloth, especially the Toba Batak ulos, has been designated as an intangible cultural heritage of Indonesia through the Decree of the Minister of Education and Culture of the Republic of Indonesia Number 270/P/2014 concerning the Determination of the 2014 Intangible Cultural Heritage of Indonesia. Apart from being regulated by this decree, traditional cultural expressions are also regulated by law. -Law Number 28 of 2014 concerning Copyright and also through Law Number 5 of 2017 concerning the Promotion of Culture which aims to advance Indonesian national culture and make Culture an investment to realize the national goals of the Indonesian nation.